2022
DOI: 10.21037/tau-22-527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a combined lncRNA prognostic signature and knockdown of lncRNA MANCR to inhibit progression of clear cell renal cell carcinoma by bioinformatics analysis

Abstract: Background Long non-coding RNAs (lncRNAs) have become potential therapeutic targets or promising prognostic biomarkers in cancers. However, individual gene does not show sufficient prognostic value for clear cell renal cell carcinoma (ccRCC). Therefore, this study aims to develop a combined prognostic lncRNA signature to the prognosis of ccRCC. Methods The transcriptome profiling data for confirmed ccRCC cases were obtained from The Cancer Genome Atlas (TCGA; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The high-risk group also had greater type I IFN response scores and less antitumor immunity in addition to increased tumor immune cell infiltration. IFN production is a major regulator of PD-L1 expression in tumor cells and host cells, and it may enhance the benefit of anti-PD-1 therapy 50 . Therefore, a diminished antitumor immune response may portend worse outcome for those at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The high-risk group also had greater type I IFN response scores and less antitumor immunity in addition to increased tumor immune cell infiltration. IFN production is a major regulator of PD-L1 expression in tumor cells and host cells, and it may enhance the benefit of anti-PD-1 therapy 50 . Therefore, a diminished antitumor immune response may portend worse outcome for those at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The research methods mainly include the collection (collection and screening), processing (editing, sorting, management, and display), utilization (calculation and simulation), and analysis of biological data ( 9 , 10 ). Experience has shown that bioinformatics technology has great application value in the screening of disease biomarkers, which is of great significance for the diagnosis, treatment, and prognosis of diseases, and can provide a more comprehensive and profound understanding of diseases ( 11 - 14 ). A recent study showed that differentially expressed genes (DEGs) were significantly enriched in metabolic pathways, oxidative phosphorylation, and extracellular matrix (ECM) receptor interactions, and were closely related to fibrosis, collagen catabolic process and inflammatory response function ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates that lncRNA plays an important role in the development and prognosis of tumors ( 16 ). Xue et al found that the mitotically-associated lncRNA MANCR could play an important influence on the progression of ccRCC by constructing a prognostic lncRNA model ( 17 ). In addition, Zhang et al found that the cuproptosis-associated lncRNA signature could be used to predict the immune infiltration and prognosis of bladder cancer patients by systematically analyzing the expression characteristics of cuproptosis-associated lncRNA ( 18 ).…”
Section: Introductionmentioning
confidence: 99%